Principles And Conditions Of Use Of New Materials In Urban Views (Case Study Abuzar Street, District 17 Of Tehran) - Sashourpour, Mahdi; Karimi, Mahdi (The Turkish Online Journal of Design Art and Communication, 2016)
By looking at the Tehran’s urban view we can understand that diversity and heterogeneity of urban facades in a variety of architectural style approaches has created a kind of culture and social identity in architecture and related concepts such lack of integrity and continuity in architecture in urban views (readability, visibility, subjective perception, visual and aesthetic continuity). Since paying attention to the structure of contemporary architecture to refresh the urban identity, needs “critical thinking” on influencing factors in the formation of concepts and architectural elements, especially urban views, so it seems necessary by knowing the hidden aspects of architecture, also in particular approach, to prepare possibility to re-read visual identity in urban facades of Tehran in compliance with the architectural elements of identity. On the other hand architecture and contemporary urban architecture, especially different grammar review that are full of internal factors and external affecting interaction and contradictions, require prior to entering the realm of criticism or analysis and critical assessment,critical, manner and attitude of the monument be determined, however, this speech only check regardless of the style of contemporary views contained in Tehran. On the basis of this research,descriptive-analytic approach and research methods analytical and physical content through data collection tool (library, documental and field research) we try, with recognizing, assessing the current situation of Tehran city views, to provide possible solutions and implementing strategies and programs of action. In this way that with using visual preference technique VPT images of urban street view and glazed selected and placed in the questionnaires have been designed.
Keywords: New materials; urban views; perspective views of the city; city views of Abuzar street-Tehran; Yeni malzemeler; kentsel görünümleri; şehrin perspektif görünümleri; şehir manzarası Abuzar,Sokak-Tahran